Comprehensive identification of potential antioxidant components in the aerial parts of Polygonum chinense L. var. hispidum using ultra high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Issue 12 (2nd June 2020) - Zhang, Hongwu; Yu, Meng; Jia, Hongmei; Zhang, Tao; Shang, Hai; Zhang, Mengli; Zhu, Ziya; Zou, Zhongmei
Abstract: The aerial parts of Polygonum chinense L. var. hispidum are one of the key herbs in Cantonese herbal tea, which is quite a common local beverage in LingNan area of China. Previous investigation has found that this herb possesses antioxidant activity and the ethyl acetate fraction of its ethanol extract shows the strongest antioxidant activity. However, little is known about its antioxidant chemical constituents. The aim of this research was to investigate the active constituents of this plant by identifying and characterizing the chemical profile in ethyl acetate fraction using ultra high performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry, which can provide characteristic ultraviolet absorption, accurate molecular weight, and diagnostic tandem mass spectrometry fragment ions. As a result, 85 compounds were identified including 22 flavonoids, 12 ellagic acids, 34 ellagitannins, 16 phenolic acids, and one phenolic amide. All the phenolic compounds identified in this work, especially ethyl gallate, geraniin, chebulagic acid, and quercitrin with the higher peak areas in the ultra high performance liquid chromatography with mass spectrometry chemical profile of this plant, could be the bioactive principles responsible for the antioxidant activity. These findings in the present study could benefit further studies involving the functions and chemicals of this plant, and provide scientific evidence for usage of Cantonese herbal tea.